A Newsvendor’s Procurement Problem when Suppliers Are Unreliable - Dada, Maqbool; Petruzzi, Nicholas C.; Schwarz, Leroy B. (Manufacturing and Service Operations Management, 2007)
We consider the problem of a newsvendor that is served by multiple suppliers, where any given supplier is defined to be either perfectly reliable or unreliable. By perfectly reliable we mean a supplier that delivers an amount identically equal to the amount desired, as is the case in the most basic variant of the newsvendor problem. By unreliable, we mean a supplier that with some probability delivers an amount strictly less than the amount desired. Our results indicate the following effects of unreliability: From the perspective of the newsvendor, the aggregate quantity ordered is higher than otherwise would be ordered if the newsvendor’s suppliers were completely reliable. From the perspective of end customers, however, the service level provided is lower than otherwise would be provided if the newsvendor’s suppliers were completely reliable. From the perspective of the suppliers, although reliability affects how much is ordered from a selected supplier, cost generally takes precedence over reliability when it comes to selecting suppliers in the first place. Even perfect reliability is no guarantee for qualification since, in an optimal solution, a given supplier will be selected only if all less-expensive suppliers are selected, regardless of the given supplier’s reliability level. Nevertheless, the relative size of a selected supplier’s order depends on its reliability.